Analisis Yuridis Pemutusan Hubungan Kerja (PHK) Tanpa Pesangon dalam Perspektif Peraturan Pemerintah Nomor 35 Tahun 2021 - Sulthan Fadhil Hisyam (PT. Saha Kreasi Indonesia, 2026)
This research provides a rigorous examination of the termination of employment policies that exempt employers from severance pay obligations under Government Regulation Number 35 of 2021. Within the framework of labor market liberalization introduced by the Job Creation Law, significant legal ambiguity has surfaced concerning the